2015
DOI: 10.1007/s00384-015-2396-2
|View full text |Cite
|
Sign up to set email alerts
|

Fecal transplant is as effective and safe in immunocompromised as non-immunocompromised patients for Clostridium difficile

Abstract: Clostridium difficile infection (CDI) is a leading cause of nosocomial infection and isassociated with significant morbidity and mortality. Immunocompromised (IC) patients are particularly at higher risk. Recurrence rates of up to 60 % have been reported after the third episode despite treatment with antibiotics. Recent published reports of fecal microbiota transplantation (FMT) in the IC population have shed light that the procedure proves to be effective and safe. No studies that compare the efficacy and adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 1 publication
2
20
0
Order By: Relevance
“…On further review, these patients included both IBD and non‐IBD patients. Our study showed that there was no statistical significant difference in the success of FMT in patients on immunosuppressive therapy when compared to patients not on immunosuppression, which is in alignment with existing literature . Although our population of patients on immunosuppression was small, our cure rate in this subset population on immunosuppression was 62.5% after first FMT compared to existing literature that has reported a cure rate of 78% .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…On further review, these patients included both IBD and non‐IBD patients. Our study showed that there was no statistical significant difference in the success of FMT in patients on immunosuppressive therapy when compared to patients not on immunosuppression, which is in alignment with existing literature . Although our population of patients on immunosuppression was small, our cure rate in this subset population on immunosuppression was 62.5% after first FMT compared to existing literature that has reported a cure rate of 78% .…”
Section: Discussionsupporting
confidence: 88%
“…Our study showed that there was no statistical significant difference in the success of FMT in patients on immunosuppressive therapy when compared to patients not on immunosuppression, which is in alignment with existing literature. 5 Although our population of patients on immunosuppression was small, our cure rate in this subset population on immunosuppression was 62.5% after first FMT compared to existing literature that has reported a cure rate of 78%. 14 Furthermore, when examining the patients with IBD, there was no statistically significant difference in the success of FMT for patients with active or inactive IBD.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In our review, we could not find any published reports of post‐FMT bacteremia after flexible sigmoidoscopy administration. Studies published on immunocompromised patients who underwent FMT (through upper gastrointestinal route or colonoscopy) did not report FMT‐related bacteremia, although only one these studies included fulminant infections …”
Section: Discussionmentioning
confidence: 99%
“…did not report FMT-related bacteremia, although only one these studies included fulminant infections. 6,7,19,20…”
Section: Studies Published On Immunocompromised Patients Who Underwenmentioning
confidence: 99%